Grading cartilage damage with diffuse reflectance spectroscopy: Optical markers and mechanical properties. Issue 3 (8th October 2022) - Rovnyagina, Nataliya R.; Budylin, Gleb S.; Dyakonov, Pavel V.; Efremov, Yuri M.; Lipina, Marina M.; Goncharuk, Yuliya R.; Murdalov, Emirkhan E.; Pogosyan, David A.; Davydov, Denis A.; Korneev, Alexander A.; Serejnikova, Natalia B.; Mikaelyan, Karen A.; et al.
Abstract: Osteoarthritis (OA) is one of the most common joint diseases worldwide. Unfortunately, clinical methods lack the ability to detect OA in the early stages. Timely detection of the knee joint degradation at the level of tissue changes can prevent its progressive damage. Here, diffuse reflectance spectroscopy (DRS) in the NIR range was used to obtain optical markers of the cartilage damage grades and to assess its mechanical properties. It was observed that the water content obtained by DRS strongly correlates with the cartilage thickness ( R = .82) and viscoelastic relaxation time ( R = .7). Moreover, the spectral parameters, including water content (OH‐band), protein content (CH‐band), and scattering parameters allowed for discrimination between the cartilage damage grades (10 −4 < P ≤ 10 −3 ). The developed approach may become a valuable addition to arthroscopy, helping to identify lesions at the microscopic level in the early stages of OA and complement the surgical analysis . Abstract : Osteoarthritis (OA) is one of the most common joint diseases worldwide. Methods of early and accurate diagnostics make it possible to provide timely and personalized treatment. Unfortunately, clinical methods lack the ability to detect OA in the early stages. This work is devoted to the development of new approach that may allow rapid detection of early stages of cartilage degradation using diffuse reflectance spectroscopy.